Indeks Inklusi Keuangan Syariah di Indonesia dan Korelasinya terhadap Kualitas Hidup Perempuan - Hidayatul Azqia; M. Mahbubi Ali; Saniatun Nurhasanah (Department Islamic Economics, 2023)
The purpose of this research: This thesis discusses and provides an overview of the Islamic financial inclusion index in Indonesia and its correlation with women's quality of life. Method: This study uses a descriptive quantitative approach with the method of calculating the Index of Sharia Financial Inclusion (ISFI) developed by Sarma, (2012) and Pearson's correlation coefficient developed by Gupta et al., (2014). The data from this study uses secondary data obtained from the publications of the Financial Services Authority, the Central Statistics Agency and the Ministry of Child Protection and Women's Empowerment of the Republic of Indonesia. The study covers 33 provinces for the 2015-2020. Findings: The results of this study found that the level of Islamic financial inclusion in Indonesia based on the 2015-2020 period was still relatively low at 0.105. Based on the observations, the provinces of DKI Jakarta and Nanggroe Aceh Darussalam, they are the most superior provinces in measuring the Islamic financial inclusion index in this study, with the acquisition value of each province respectively 0.531 and 0.435 or in other words, only these 2 provinces are included in the list. the remaining medium category is provinces with a low financial inclusion category. On the other hand, East Nusa Tenggara province occupies the lowest position in the Islamic financial inclusion index level with an index score of only 0.002. This study also found that the Islamic financial inclusion index (ISFI) has a positive relationship to women's quality of life (IPG) with an r-Pearson value of 0.261, the ISFI coefficient value of 7.811 and a significance of 0.0002 (smaller than alpha 0.05). These results indicate that changes in the level of Islamic financial inclusion will result in changes in women's quality of life (IPG) in the same direction or if the ISFI index increases by one unit it will increase the GPA index by 7.811.